2022
DOI: 10.3390/molecules27144622
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols from the Peels of Punica granatum L. and Their Bioactivity of Suppressing Lipopolysaccharide-Stimulated Inflammatory Cytokines and Mediators in RAW 264.7 Cells via Activating p38 MAPK and NF-κB Signaling Pathways

Abstract: Punica granatum L. (Punicaceae) is a popular fruit all over the world. Owning to its enriched polyphenols, P. granatum has been widely used in treating inflammation-related diseases, such as cardiovascular diseases and cancer. Twenty polyphenols, containing nine unreported ones, named punicagranins A–I (1–9), along with eleven known isolates (10–20), were obtained from the peels. Their detailed structures were elucidated based on UV, IR, NMR, MS, optical rotation, ECD analyses and chemical evidence. The potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…L-NAME and Dexamethasone (10 µM) were used as positive controls, and suppressed the LPS induced levels of nitric oxide from 80.38 µM to 45.61 µM and 44.5 µM, respectively. While as 1 suppresses the release of NO to 23.29 µM at 10 μM, 36.26 at 5 µM, 48.65 at 1 µM; JR-9, on the other hand, suppresses the same to 16.43 µM at 10 µM, 31.62 at 5 µM, 40.97 at 1 µM proving JR-9 to be the better nitric oxide inhibitor as compared to 1 [27].…”
Section: Arteannuin-b (1) and Jr-9 Inhibited The Production Of No Tnf...mentioning
confidence: 89%
“…L-NAME and Dexamethasone (10 µM) were used as positive controls, and suppressed the LPS induced levels of nitric oxide from 80.38 µM to 45.61 µM and 44.5 µM, respectively. While as 1 suppresses the release of NO to 23.29 µM at 10 μM, 36.26 at 5 µM, 48.65 at 1 µM; JR-9, on the other hand, suppresses the same to 16.43 µM at 10 µM, 31.62 at 5 µM, 40.97 at 1 µM proving JR-9 to be the better nitric oxide inhibitor as compared to 1 [27].…”
Section: Arteannuin-b (1) and Jr-9 Inhibited The Production Of No Tnf...mentioning
confidence: 89%
“…[65] However, when cells receive various external stimuli, receptors on the cell membrane translocate into the cytoplasm, and iκB is phosphorylated by binding to the iκB kinase complex, so as to activate the NF-κB signaling pathway, at which time NF-κB moves into the nucleus and induces transcription of related genes. [66] Moreover, activated NF-κB signaling pathway can also induce biological reactions in related factors, such as IL-6, tumor necrosis factor-α (TNF-α), chemokines, inflammatory mediators nitric oxide (NO), prostaglandin E2, inducible cyclooxygenase-2, adhesion factors, inflammatory enzymes, immune receptors, apoptotic genes, proliferation-regulating genes, signal transduction genes, anti-oxidative stress-related genes, [67] so as to further amplify the inflammatory response. [68] And the long-standing inflammatory reactions will mutate tumor suppressor genes in normal cells, eventually promote tumor formation.…”
Section: Nf-κb Signaling Pathwaymentioning
confidence: 99%
“…Cells via Activating p38 MAPK and NF-κB Signaling Pathways. (30) It was reported that the Plant flower extracts were tested for their anti-inflammatory effects by determining the ability to inhibit the activity of lipoxygenase and proteinase. They are characterized by the ability to inhibit lipoxygenase at a level above 80% and proteinase at the level of about 55%.…”
Section: Antimicrobial Activitymentioning
confidence: 99%